Unreduced Male Gamete Formation in Cymbidium and Its Use for Developing Sexual Polyploid Cultivars - Zeng, Rui-Zhen; Zhu, Jiao; Xu, Shi-Ying; Du, Guo-Hui; Guo, He-Rong; Chen, Jianjun; Zhang, Zhi-Sheng; Xie, Li (Frontiers in Plant Science, 2020)
Polyploidy plays an important role in crop improvement. Polyploid plants, particularly those produced through unreduced gametes (2n gametes), show increased organ size, improved buffering capacity for deleterious mutations, and enhanced heterozygosity and heterosis. Induced polyploidy has been widely used for improving floriculture crops, however, there are few reported sexual polyploid plants in the floriculture industry. This study evaluated nine cultivars of Cymbidium Swartz and discovered that 2n male gametes occurred in this important orchid. Depending on cultivars, 2n male gamete formation frequencies varied from 0.15 to 4.03%. Interspecific hybrids generally produced more 2n male gametes than traditional cultivars. To generate sexual polyploid plants, seven pairs of crosses were made, which produced five triploid and two tetraploid hybrids. Two triploid hybrids were evaluated for in vitro regeneration and growth characteristics. Compared to the diploid parents, the triploids were more easily regenerated through rhizomes or protocorms, and regenerated plants had improved survival rates after transplanting to the greenhouse. Furthermore, the sexual polyploid plants had more compact growth style, produced fragrant flowers, and demonstrated heterosis in plant growth. Through this study, a reliable protocol for selection of appropriate parents for 2n gamete production, ploidy level evaluation, in vitro culture of polyploid progenies, and development of new polyploid cultivars was established. Our study with Cymbidium suggests that the use of 2n gametes is a viable approach for improving floriculture crops.